Experimental and Numerical Investigation of Integrated Steel Shear Walls with Varying Web Width-to-Thickness Ratios - Lee, Doo Yong; Cho, Bong Ho; Jung, Dam I. (Advances in Materials Science and Engineering, 2023)
The cold-formed steel-framed shear wall sheathed with steel sheet is widely used as a lateral force-resisting system for light-framed construction. However, the boundary conditions of the screw joint are not clear when steel is screwed to the frame. To address this issue, experimental methods have been used to calculate shear strength, but these methods have many limiting factors. In this study, we investigate the structural performance of integrated steel shear walls with varying web width-to-thickness ratios as an alternative to steel-sheathed shear walls used in light-gauge steel frames. The proposed design equation for cold-formed steel integrated shear walls is validated by three specimens and 72 finite element models. This equation allows designers to determine the strength of integrated steel shear walls without conducting full-scale shear-wall tests.
Keywords: Cold-formed steel; Experimental investigations; Experimental methods; Lateral force resisting system; Numerical investigations; Screw joints; Steel shear walls; Steel-framed; Web width; Width-to-thickness ratio